Physical Activity Monitoring Model to Measure the Appropriateness of Weekly Physical Activity for the World Health Organization’s Physical Well-Being and Health Claims - Rosario Ceruso; Giuseppe Giardullo; Giuseppe Di Lascio; Pompilio Cusano; Italo Sannicandro (Physical Education Theory and Methodology)
Objectives. The study aimed to test an agile monitoring tool to correlate physical activity levels for the 2 target age groups of school education with energy consumption.